Avaliação do impacto da inundação na resistência e deformabilidade de um solo laterítico e colapsível: estudo experimental e numérico - Falcão, Patrícia Rodrigues (2021)
In the northern region of the state of Rio Grande do Sul it is common the presence of lateritic soils of medium to clayey texture, unsaturated and with high porosity. The change in the humidity in this type of soil is linked to the loss of suction. Therefore, the stress-strain behavior exhibits a high complexity resulting in design uncertainties. The inundation damages the soil structure causing a reduction in the soil volume, and this phenomenon is called collapse. In this context, a foundation built on this ground may be subject to differential settlements that will consequently generate pathologies in the buildings. It is relevant to point out that cracks and fissures are commonly observed in the city of Cruz Alta after some event that culminated in soil flooding. This panorama demonstrates the notorious importance of studying the intervening factors in a foundation project. Thus, the present dissertation aimed at a geotechnical investigation program with the purpose of understanding the peculiarities of the soil. To this end, the Geotechnical Engineering Experimental Field, located on the UNICRUZ campus, was used. Laboratory tests were performed for characterization, X-ray diffraction, mineralogical analysis of the granular fraction, characteristic curves, confined compression, direct shear and triaxial compression. In the field, SPT tests were performed with and without water circulation and slow-load static load testing with inundation of the underlying soil. Using the PLAXIS 2D computational tool, 2D numerical models were created and validated using the test results. The confined compression tests with flooding indicate that the soil is potentially collapsible. Shear strength is linked with suction since there is a high magnitude reduction in the cohesive intercept. The results of the SPT measurements can provide a suggestive tool for understanding that flooding will lead to a loss of soil suction. The load tests on piles carried out with pre- flooding demonstrated a significant reduction in bearing capacity. The results of the analyses demonstrate the importance of the study of unsaturated soils for foundation projects.